Positive Childbirth Experience: A Scoping Review - Ana Claudia da Costa Guterres; Farida Kartini; M. Hakimi; Joaquim Pinto; Arina Chusnatayaini (Universitas STRADA Indonesia, 2025)
Background: A positive childbirth experience, stating that it must meet or exceed a woman's personal and socio-cultural beliefs and expectations. This includes giving birth to a healthy baby in a clinically and psychologically safe environment, with ongoing practical and emotional support from birth attendants and competent clinical staff. Purpose: This scoping review aimed to identify the best evidence about positive experiences during childbirth, evaluating what factors control and contribute to positive experiences during childbirth. Methods: Databases were searched from 2019 to 2023 from various databases, including PubMed, ScienceDirect, and Cochrane Library/Wiley. As well as using search engines such as Google Scholar and Research Rabbit and selecting them using Rayyan assistance. Critical appraisal and data charting are adopted from the JBI checklist, including cross-sectional, and Qualitative method. Of the 1600 articles identified, only Six met the criteria. Results: The results of this review identified two themes and four subthemes. The two themes are including factors controlling and contribute, and four subthemes such us support and communication factor, participation and empowerment, medical factor and psychology factors. Conclusion: Recommendation for health professionals, especially midwives, is to continue to develop a good and holistic service strategy, by providing support, empowering mothers and also providing good support in order to improve the positive experience during childbirth and minimize negative feedback during childbirth.